Deworming the grinder for successful extrication of a mangled hand: a case report - Md Yusoff, Zuhri (USIM Press, 2021)
Grinding machine injuries are known to cause severe mutilating injuries of the upper limb. In some cases, the machinery equipment may still be attached to the limb when the patient reaches the hospital. In treating these injuries, the patient’s hemodynamic status should be the first priority of resuscitation. Following this and whenever possible, a reversal of the grinding mechanism should be done to free the limb. This would allow assessment of the extent of zone-of-injury prior to starting the surgical procedure. We report a case of a 28-year-old male who sustained a mangled hand injury that was successfully extricated from an industrial grinding machine, thereby allowing preservation of precious length of the limb during surgery. This case highlights the importance of adhering to safety precautions at the workplace to reduce the risk of potential occupational hazards when dealing with machinery equipment.